Biosynthesis of Phenolic Compounds and Antioxidant Activity in Fresh-Cut Fruits and Vegetables - Hu, Wenzhong; Sarengaowa,; Guan, Yuge; Feng, Ke (Frontiers in Microbiology, 2022)
Phenolic compounds are secondary metabolites and widely distributed in higher plants. When plants are subjected to injury stress, the rapid synthesis of more phenols is induced to result in injury defense response for wound healing and repair. Fresh-cut fruits and vegetables undergo substantial mechanical injury caused by pre-preparations such as peeling, coring, cutting and slicing. These processing operations lead to activate the biosynthesis of phenolic compounds as secondary metabolite. Phenolic compounds are important sources of antioxidant activity in fresh-cut fruits and vegetables. The wound-induced biosynthesis and accumulation of phenolic compounds in fresh-cut fruits and vegetables have been widely reported in recent years. This article provides a brief overview of research published over the last decade on the phenolic compounds and antioxidant activity in fresh-cut fruits and vegetables. It is suggested that fresh-cut processing as mechanical wounding stress can be used as an effective way to improve the nutritional composition and function of fresh-cut produces.